2021
DOI: 10.5194/amt-14-7627-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evolution under dark conditions of particles from old and modern diesel vehicles in a new environmental chamber characterized with fresh exhaust emissions

Abstract: Abstract. Atmospheric particles have several impacts on health and the environment, especially in urban areas. Parts of those particles are not fresh and have undergone atmospheric chemical and physical processes. Due to a lack of representativeness of experimental conditions and experimental artifacts such as particle wall losses in chambers, there are uncertainties on the effects of physical processes (condensation, nucleation and coagulation) and their role in particle evolution from modern vehicles. This s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The chemical and physical processes are commonly studied in smog chambers to calculate SOA formation yields and the effect of after-treatment systems ( Figure 10 ). A recent study under dark conditions [ 173 ] showed the physical evolution of particles characterised during 6 to 10 h from Euro 3 to Euro 6 vehicles. An increase in particle mass was observed even without photochemical reactions due to the presence of intermediate-volatility organic compounds and SVOCs.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…The chemical and physical processes are commonly studied in smog chambers to calculate SOA formation yields and the effect of after-treatment systems ( Figure 10 ). A recent study under dark conditions [ 173 ] showed the physical evolution of particles characterised during 6 to 10 h from Euro 3 to Euro 6 vehicles. An increase in particle mass was observed even without photochemical reactions due to the presence of intermediate-volatility organic compounds and SVOCs.…”
Section: Scientific Backgroundmentioning
confidence: 99%